Evaluating the transmission risk of SARS-CoV-2 from sewage pollution - Ransome, E; Robbs, F; Jones, S; Coleman, CM; Harris, ND; Woodward, G; Bell, T; Trew, J; Kolarević, S; Kračun-Kolarević, M; Savolainen, V (Elsevier, 2022)
The presence of SARS-CoV-2 in untreated sewage has been confirmed in many countries but its incidence and infection risk in contaminated waters is poorly understood. The River Thames in the UK receives untreated sewage from 57 Combined Sewer Overflows (CSOs), with many discharging dozens of times per year. This study investigated if such discharges provide a pathway for environmental transmission of SARS-CoV-2. Samples of wastewater, surface water, and sediment collected close to six CSOs on the River Thames were assayed over eight months for SARS-CoV-2 RNA and infectious virus. Bivalves were also sampled as an indicator species of viral bioaccumulation. Sediment and water samples from the Danube and Sava rivers in Serbia, where raw sewage is also discharged in high volumes, were assayed as a positive control. No evidence of SARS-CoV-2 RNA or infectious virus was found in UK samples, in contrast to RNA positive samples from Serbia. Furthermore, this study shows that infectious SARS-CoV-2 inoculum is stable in Thames water and sediment for <3 days, while SARS-CoV-2 RNA is detectable for at least seven days. This indicates that dilution of wastewater likely limits environmental transmission, and that detection of viral RNA alone is not an indication of pathogen spillover.